Flat lamp fabrication using thermal grown carbon nano tubes - Lee, D.-J.; Ju, B.-K.; Lee, Y.-H.; Yoo, J.-E.; Min, B.-D.; Park, J.-H.; Kim, B.-C.; Jang, J.; Oh, M.-H. (SID Conference Record of the International Display Research Conference, 2021)
We fabricated 1-inch CNTs flat lamp as diode and triode structure. The CNTs are grown on soda-lime glass substrate. In the case of triode structure, the grid was inserted between anode and cathode plate to dispersion of emitted electron and decreasing of turn on voltage. Also, the electric field distribution in panel was simulated using a maxwell simulator. And, we will introduce the direct joint method, which need not exhausting tube and hole. The CNTs-lamps are successfully packaged by both method and observed light emission of about 9. 8Kcd/m2 brightness.